High prevalence of unusual KRAS, NRAS, and BRAF mutations in POLE‐hypermutated colorectal cancers - Favre, Loetitia; Cohen, Justine; Calderaro, Julien; Pécriaux, Adrien; Nguyen, Cong‐Trung; Bourgoin, Rémi; Larnaudie, Laura; Dupuy, Aurélie; Ollier, Marie; Lechapt, Emmanuèle; Sloma, Ivan; Tournigand, Christophe; et al. (Molecular Oncology, 2022)
Exonucleasic domain POLE (edPOLE) mutations, which are responsible for a hypermutated tumor phenotype, occur in 1–2% of colorectal cancer (CRC) cases. These alterations represent an emerging biomarker for response to immune checkpoint blockade. This study aimed to assess the molecular characteristics of edPOLE‐mutated tumors to facilitate patient screening. Based on opensource data analysis, we compared the prevalence of edPOLE mutations in a control group of unselected CRC patients (n = 222) vs a group enriched for unusual BRAF/RAS mutations (n = 198). Tumor mutational burden (TMB) and immune infiltrate of tumors harboring edPOLE mutations were then analyzed. In total, 420 CRC patients were analyzed: 11 edPOLE‐mutated tumors were identified, most frequently in microsatellite (MMR)‐proficient young (< 70 years) male patients, with left‐sided tumors harboring noncodon 12 KRAS mutation. The prevalence of edPOLE‐mutated tumors in the control vs the experimental screening group was, respectively, 0.45% (n = 1) vs 5.0% (n = 10). Among the 11 edPOLE‐mutated cases, two had a low TMB, three were hypermutated, and six were ultramutated. EdPOLE‐mutated cases had a high CD8+ tumor‐infiltrating lymphocyte (TIL) infiltration. These clinicopathological and molecular criteria may help to identify edPOLE mutations associated with a high TMB in CRC, and improve the selection of patients who could benefit from immunotherapy.